Standard symbols for welding, brazing and nondestructive examination (American Welding Society ; Reproduced by World Engineering Xchange (WEX) with the permission of AWS under royalty agreement, 2007)
"This standard establishes a method for specifying certain welding, brazing, and nondestructive examination information by means of symbols. Detailed information and examples are provided for the construction and interpretation of these symbols. This system provides a means of specifying welding or brazing operations as well as nondestructive examination, including the examination method, frequency, and extent."
"AWS A2.4:2007."
"An American national standard."
"Supersedes ANSI/AWS A2.4-98."
"Approved by the American National Standards Institute March 23, 2007."
Keywords: Welding -- Notation.; Welded joints -- Drawings.; elektronické knihy; electronic books